2016
DOI: 10.1016/j.cell.2016.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Loss of Function in a Limb Enhancer during Snake Evolution

Abstract: The evolution of body shape is thought to be tightly coupled to changes in regulatory sequences, but specific molecular events associated with major morphological transitions in vertebrates have remained elusive. We identified snake-specific sequence changes within an otherwise highly conserved long-range limb enhancer of Sonic hedgehog (Shh). Transgenic mouse reporter assays revealed that the in vivo activity pattern of the enhancer is conserved across a wide range of vertebrates including fish, but not in sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
298
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(307 citation statements)
references
References 86 publications
(119 reference statements)
7
298
0
2
Order By: Relevance
“…Pairs of single guide RNAs (sgRNAs) targeting genomic sequence 5′ and 3′ of the sequence to be deleted were designed using CHOPCHOP 45 (see Supplementary Table 1 for sgRNA sequences and coordinates of deleted regions). Knockout mice were engineered as described previously 46 using a mix containing Cas9 mRNA (final concentration of 100 ng/ul) and two sgRNAs (25 ng/ul each) in injection buffer (10 mM Tris, pH 7.5; 0.1 mM EDTA). This mix was injected into the cytoplasm of single-cell FVB strain mouse embryos.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pairs of single guide RNAs (sgRNAs) targeting genomic sequence 5′ and 3′ of the sequence to be deleted were designed using CHOPCHOP 45 (see Supplementary Table 1 for sgRNA sequences and coordinates of deleted regions). Knockout mice were engineered as described previously 46 using a mix containing Cas9 mRNA (final concentration of 100 ng/ul) and two sgRNAs (25 ng/ul each) in injection buffer (10 mM Tris, pH 7.5; 0.1 mM EDTA). This mix was injected into the cytoplasm of single-cell FVB strain mouse embryos.…”
Section: Methodsmentioning
confidence: 99%
“…To assess spatial changes in gene expression in mouse embryonic limbs, whole mount in situ hybridization using digoxigenin-labeled antisense riboprobes was carried out as previously described 46 . Forelimbs and hindlimbs from at least three independent embryos were analyzed for each genotype (including wild-type littermate controls).…”
Section: Methodsmentioning
confidence: 99%
“…Earlier work suggested that the limb fails to grow because of a degeneration of the AER resulting in the lack of Fgf and Shh production breaking the ectodermal-mesenchymal Fgf positive feedback loop (Cohn and Tickle, 1999). Recently, however, it was been discovered that pythons do initially induce Shh and Fgf8 in early hindlimb buds, only transiently and Shh expression is reduced due to degeneration of the ZRS (Kvon et al, 2016; Leal and Cohn, 2016). Further analysis revealed that a conserved Ets1 binding site in the ZRS is lost in all examined snake genomes and restoration of this site is sufficient to rescue the full activity of the ZRS (Kvon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, it was been discovered that pythons do initially induce Shh and Fgf8 in early hindlimb buds, only transiently and Shh expression is reduced due to degeneration of the ZRS (Kvon et al, 2016; Leal and Cohn, 2016). Further analysis revealed that a conserved Ets1 binding site in the ZRS is lost in all examined snake genomes and restoration of this site is sufficient to rescue the full activity of the ZRS (Kvon et al, 2016). These findings reopen the question of why the limb is lost when both Shh and Fgf are expressed in the initial limb bud?…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Leal and Cohn [2016] proposed that hind limb development stops in python embryos as a result of mutations that eliminate essential transcription factor binding sites in the limb-specific enhancer of Sonic hedgehog. Consistently, Kvon et al [2016] demonstrated that through nucleotide-specific changes in the zone of polarizing activity regulatory sequence (ZRS, which is a limb-specific enhancer of Sonic hedgehog) in snakes the ZRS enhancer has progressively lost its function during snake evolution, leading to the disappearance of the limbs. In contrast, according to Leal and Cohn [2016], Hoxd limb enhancers are conserved in the python embryo.…”
Section: Hox Genes In Reptile Developmentmentioning
confidence: 88%